India field visit by CCAFS Researchers 2014 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
CCAFS Program Director Bruce Campbell, theme leaders Andy Jarvis and Phil Thronton, and Science Officers John Recha and Daisy Martinez, along with CCAFS South Asia Regional Program Leader Pramod Aggarwal, and scientists from other CGIAR centres traveled to Haryana and Maharashtra states in India to visit Climate-Smart Villages and interact with national and local partners and farmers.